(3CSFdI hCLhHI dCHf GdYQHi hcdGeg aj ehVhYGJ TJis - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3SCdJ QMec Gddg hEjGfG gPI GdGSFdI hCfG Ef TGA Gddg GLjH Yf HYVgG GdSDGd GdChd eG GdaQb Hjf GdaJQI hGdhbaI ? s
(3BNQgG (B:s
(3djS GdJced ai GdYjfjf cGcMd Gddg GcHQ aeG GSGAJ aCjf aVdc hGdeQhI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(4/594) s
Keywords: (3GdadSaI hGdefWbs